2018
DOI: 10.1097/acm.0000000000002005
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Educator Portfolio: An Innovative Criteria-Based Model

Abstract: The authors plan to increase awareness of the EP 2.0 template by educating promotions committees and faculty at UCSF and partnering with other institutions to disseminate it for use. They also plan to study the impact of the template on supporting educators by making their important scholarly contributions available for peer review, providing guidance for professional development, and decreasing disparities in promotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Most importantly, document your activities, their impact, and their outcomes in a format consistent with your sponsoring institution's guidelines. Consider an educator's portfolio and update your documentation at least twice yearly 5. 4.…”
mentioning
confidence: 99%
“…Most importantly, document your activities, their impact, and their outcomes in a format consistent with your sponsoring institution's guidelines. Consider an educator's portfolio and update your documentation at least twice yearly 5. 4.…”
mentioning
confidence: 99%
“…13 The educator portfolio is often used as a developmental tool to aid an educator in reflection, 4,13–16 and it may also be used for evaluation by other educators. 13,17 In 2019, Ryan et al reported that less than half of medical schools used an educator portfolio. 18…”
mentioning
confidence: 99%
“…13 The educator portfolio is often used as a developmental tool to aid an educator in reflection, 4,[13][14][15][16] and it may also be used for evaluation by other educators. 13,17 In 2019, Ryan et al reported that less than half of medical schools used an educator portfolio. 18 Although portfolios privilege the attitudes and activities of educators, we have come to question whether educator portfolios offer the optimal way to present the accomplishments of non-research-oriented activities for the purposes of promotion.…”
mentioning
confidence: 99%
“…7 These educational excellence portfolios highlight an individual’s academic excellence in teaching and evaluation, development and dissemination of enduring education products, and educational leadership roles and awards. 8,9 However, interprofessional faculty who work primarily in clinical settings with other health care professionals but with few students and trainees cannot use educational portfolios to document their professional excellence for academic promotion and advancement. A previously developed QI portfolio, the first of its kind, was developed more than a decade ago, in 2009, by the Society of General Internal Medicine (SGIM) 10 for a physician audience and has had some adoption across health professions.…”
mentioning
confidence: 99%
“…Consensus was defined as an average score over 8.0. Panelists in the second round achieved consensus, with average scores of 8.4 in comprehensiveness and 8.3 in clarity (range, [6][7][8][9]. The finalized portfolio includes the following sections: personal statement; health care improvement training and certification; leadership and administrative roles; health care improvement project activities; health care improvement coaching, teaching, and curricular activities; health care improvement honors, awards, and recognitions; and supporting documents.…”
mentioning
confidence: 99%